AACN CSI Academy, part 3: Introducing the Massachusetts CSI Nursing Delirium Collaborative. Issue 11 (November 2015) - DiLibero, Justin; Edwards, Erica; Hanson, Dave
Abstract : In the final installment of our three-part series, we reveal how the Boston cohort of the American Association of Critical-Care Nurses (AACN) Clinical Scene Investigator (CSI) Academy launched a collective to improve patient safety and quality outcomes related to delirium. Abstract : The Boston cohort of the AACN CSI Academy launched a collective to improve patient safety and quality outcomes related to delirium.